THE INFLUENCE OF BRAND IMAGE AND PRODUCT DESIGN ON PURCHASE DECISIONS FOR BUAHVITA THROUGH PRODUCT QUALITY - Hardianti, Adisty Riska; Hendrawan, Diky Angga; Ramadhan, Muhammad Bagus; Bahar, Moch. Fachrudin; Putro, Dita Riyanto (Indonesian Journal Of Business And Economics, 2024)
Through product quality, this study examines how brand perception and product design affect consumers' decisions to buy Buahvita. The purchase decision is the study's dependent variable, and brand image and product design are its independent factors. On the other hand, product quality serves as a moderating factor. One hundred questionnaires from residents of one of Kediri City's housing complexes were gathered and processed. Using the convenience sampling approach, which selects people who are available and in place throughout the research period, the researcher selects the closest person to serve as a research sample until the target sample size is reached. This study was carried out in phases. Finding hypotheses in the literature or by employing descriptive statistics and gathering information from the items under study is the first step. The second stage is to test the feasibility of the data using the Validity Test and Reliability Test. The third stage is the hypothesis testing stage both partially and simultaneously. Furthermore, the adjusted determination coefficient and regression equation from the research data are calculated. The results of this study indicate that product design has a significant effect on purchasing decisions, brand image has a significant effect on purchasing decisions. Product design and brand image together have a significant influence on purchasing decisions. Product quality as a moderating variable is not able to strengthen (weaken) product design on purchasing decisions